Czy celiakia wpływa na układ rozrodczy kobiet? Krótki raport - Harvanová, Gabriela; Duranková, Silvia (Alergologia Polska - Polish Journal of Allergology, 2023)
Celiac disease is an autoimmune disorder in which gluten is the main trigger of the disorder. It enters the body through foods made from wheat, rye or barley. A patient who is positive for celiac disease suffers from several disorders after ingesting gluten, such as cramps, nausea, bloating, diarrhoea, constipation, lack of appetite. It has been shown that this disorder can affect other systems besides the gastrointestinal tract, for example, the reproductive system. It can cause complications in pregnancy, miscarriage or infertility. In this study, we focused on investigating this disease in the adult population, specifically in women who have had at least one pregnancy. We specifically investigated whether any complications occurred during pregnancy, whether the woman followed a gluten-free diet during pregnancy, and whether the baby tested positive for celiac disease after birth.